CRYPTO ASSETS AS FIDUCIARY COLLATERAL - Cornelis, Vieta Imelda; Astutik, Sri; Indra , Silvester Novalino (Hukum Responsif, 2024)
the legality of cryptoassets as collateral in debts and receivables in Indonesia. Cryptocurrencies, which continue to evolve as digital financial instruments, have posed new challenges to the traditional legal system. In the context of debt and credit, the legality of using crypto assets as collateral is questionable due to the absence of clear and specific regulations. This research uses a normative juridical approach by analysing existing laws and regulations and related literature. The results show that although crypto assets have not been explicitly regulated in Indonesian law, the potential for their use as collateral for debt and credit remains with certain conditions. To realise legal certainty, more specific regulations related to crypto assets are needed, including monitoring mechanisms and regulation of their use as collateral. This is important to protect the interests of creditors and debtors and maintain financial system stability.